2022
DOI: 10.1111/jocd.15171
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of energy‐based interventions with low‐dose isotretinoin for the treatment of inflammatory acne: An retrospective cohort analysis

Abstract: Background The combined use of oral isotretinoin with energy‐based interventions including fractional microneedle radiofrequency, pulsed dye laser, and ablative fractional laser is an effective way to treat moderate‐to‐severe inflammatory acne lesions. However, studies regarding its efficacy and safety are limited. Aims This study aimed to assess the efficacy and safety of a treatment using low‐dose isotretinoin with energy‐based interventions for inflammatory acne. Patients and Methods This retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… 2 10 12 13 Meanwhile, several studies have reported improvements in inflammatory acne assessed by acne severity scoring or lesion counts with FMR treatment. 8 11 In our study, the FMR+AFL treatment demonstrated superior efficacy compared to AFL monotherapy in patients with both inflammatory acne and post-acne scars. The gap in improvement rate for inflammatory acne and acne scars between the two methods was more prominent in the follow-up period ( Figs.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“… 2 10 12 13 Meanwhile, several studies have reported improvements in inflammatory acne assessed by acne severity scoring or lesion counts with FMR treatment. 8 11 In our study, the FMR+AFL treatment demonstrated superior efficacy compared to AFL monotherapy in patients with both inflammatory acne and post-acne scars. The gap in improvement rate for inflammatory acne and acne scars between the two methods was more prominent in the follow-up period ( Figs.…”
Section: Discussionmentioning
confidence: 59%
“…We have previously reported the real-world practice of the combined use of low-dose isotretinoin and different modes of energy-based interventions. 11 As the FMR+AFL treatment showed inhibitory effect on sebum secretion, reduced acne lesions, and improved scar texture, it can be considered a promising treatment option for personalized medicine, with or without pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining FRFM with isotretinoin is particularly effective in treating inflammatory acne and reducing scarring [ 83 ]. In fact, combinations of isotretinoin with other energy-based devices including PDL and ablative fractional lasers are effective treatments for active inflammatory acne as well [ 84 ]. Lastly, microneedling devices may be implemented in the transdermal delivery of topical retinoids and salicylic acid and for improving scarring [ 85 ].…”
Section: Methodsmentioning
confidence: 99%
“…Non-ablative fractionated radiofrequency microneedling (FRFM) and combinations with isotretinoin have been effective in treating active acne and reducing scarring, with the adjunctive use of microneedling facilitating the enhanced delivery of topical treatments (retinoids and salicylic acid) and scar improvement [272][273][274][275]. Using isotretinoin in conjunction with other energy-based devices such as PDL and ablative fractional lasers has also been proven effective in managing active inflammatory acne [276].…”
Section: Procedural Therapiesmentioning
confidence: 99%